Coupling superconducting magnet and refrigerator thermal-hydraulic models for nuclear fusion applications. (April 2019) - Bonifetto, R; Brighenti, A; Savoldi, L; Zanino, R
Abstract: Helium refrigerators will provide the needed cooling power to the superconducting magnets of future magnetic fusion reactors, e.g. ITER, JT-60SA, EU DEMO. Reliable simulation tools are required to model the magnets-refrigerator coupling, in order to cope with feedbacks affecting the overall system dynamics. Here we couple the 4C code for the analysis of thermal-hydraulic transients in superconducting magnets with a refrigerator model developed in Modelica. The results of the new tool are compared with experimental data from the first phase of an ITER CSMC cool-down, from 300 K to 80 K.